Evaluation of soybean germplasms for resistance to stay-green syndrome - Xiaojie Zhu; Wen Wang; Huawei Gao; Ranran Liu; Yating Geng; Yixin Zhu; Guofu Liu; Qianqian Yu; Shulei Wang; Chongyang Li; Like Liu (Scientific Reports)
Abstract Stay-green syndrome (SGS) resistant germplasms serve as the cornerstone for soybean improvement. A comprehensive assessment was conducted on a panel of 1553 germplasms to evaluate their resistance to SGS through natural inoculation. Over a three-year period, one landrace, ZaoShuHeiDou, emerged as resilient to SGS, displaying a significantly reduced risk of SGS (p < 0.05) compared to its counterparts. The broad-sense heritability of SGS resistance was 0.86. Notably, landraces demonstrated a substantially lower incidence of SGS compared to improved cultivars. Furthermore, the severity of SGS correlated with several key traits pertinent to soybean improvement efforts. In field trials, the application of insecticides effectively mitigated SGS severity, whereas the use of organic fertilizers and soil sterilization had no discernible impact. A total of 83 DNA samples were successfully amplified from SGS-afflicted plants using specific primers for soybean stay-green associated virus (SoSGV), and a SoSGV LCU-1 strain was isolated. The qPCR analysis confirmed a positive correlation between SGS severity and the relative SoSGV copy number in afflicted plants. The findings of this study lay a solid foundation for the development of SGS-resistant cultivars and the exploration of underlying resistance mechanisms.